Integrating Civic Themes into English Language Instruction: A Task-Based Approach to Enhancing Academic Literacy - Himala Praptami Adys; Seny Luhriyani Sunusi; Geminastiti Sakkir (Journal of Excellence in English Language Education, 2026)
The integration of discipline-specific content into English for Specific Purposes (ESP) instruction has emerged as a pivotal pedagogical strategy in higher education, yet empirical evidence regarding its implementation in civic education contexts remains scarce. This article reports on a task-based pedagogical intervention designed to enhance academic literacy among Indonesian civic education students through the integration of civic themes into ESP instruction. Drawing upon data from 82 second-semester students at Universitas Negeri Makassar, the study employed a mixed-methods design combining vocabulary discovery tasks, text analysis, and academic writing exercises centered on authentic civic-themed articles. Findings reveal that while the task-based approach facilitated meaningful engagement with civic content and disciplinary vocabulary, persistent challenges emerged, including students' tendency to select generic civic vocabulary rather than to explore specialized terminology and their increasing reliance on artificial intelligence tools for writing tasks rather than developing independent academic expression. These findings contribute to the growing body of ESP research by demonstrating both the affordances and limitations of content-language integration in civic education contexts. The study proposes a refined pedagogical framework that balances content engagement with explicit academic literacy development, addressing the identified gaps while leveraging the motivational potential of civic themes.